The Role of Nurses in Managing an Age-Friendly Health System (AFHS) in Hospitals - Jaipang , Chulaluk; Udchumpisai, Monthira; Thanthitaweewat, Natthasa (Journal of The Royal Thai Army Nurses, 2025)
Thailand is now entering a fully aged society. Older adults commonly have chronic illnesses and health issues that require ongoing hospitalization. The traditional health service for older adults delivers care in fragmented silos based on specialties and symptoms rather than aligning with patients’ life goals and individualized needs, resulting in key geriatric issues being incompletely or inconsistently assessed and managed across care settings. Therefore, nurses must develop care models that meet the needs of older people in society. This article aims to present the role of nurses in organizing age-friendly health services in hospitals based on the 4Ms framework. This concept emphasizes four key areas of care for older adults: 1) focusing on what matters to the patient, 2) ensuring appropriate medication use, 3) promoting mental health and cognitive function, and 4) encouraging mobility. These address common issues encountered among hospitalized older adults. Additionally, this article discusses the integration of the age-friendly health service system in hospitals with the five steps of the nursing process (assessment, diagnosis, planning, implementation, and evaluation). This is to enable nurses to apply the age-friendly concept comprehensively in the care of older adults. The article also covers strategies for nursing administrators to successfully develop and sustain age-friendly health service systems in hospitals. Such development and management will contribute to better health and well-being for older people in Thai society.